A Wideband Low profile Metasurface based Folded Transmitarray Antenna - Chatterjee S.; Gupta Y.; Bhattacharyya S. (My University, 2025)
In this present work, a wideband folded transmitarray (FTA) antenna has been proposed by using a low-profile metasurface (MS) array. The FTA is composed of a transmitarray (TA) based on four distinct meta-atoms (MAs) yielding mutual phase difference of 90° and a host reflect array (RA) to operate over the range 10 GHz to 15 GHz. The TAs have been realized incorporating 45° rotated cross dipoles with square ring corner cut designed on the F4B substrate while the other two layers of the substrate are metallized with orthogonal alignment. Similarly, the RAs has been designed by using a dipole with 45° rotation. An open-ended waveguide (OW) is used as a feeder for the FTA antenna which is placed in the center of the RA. The proposed FTA exhibits peak realized gain of 19.23 dBi with an aperture efficiency of 38.5% together with a 1-dB gain bandwidth of 40% referred to its center frequency of 12.5 GHz. The design is potentially used in radar, synthetic aperture radar (SAR), satellite communication, and radio astronomy. © 2023 IEEE.